Contagion between Islamic and conventional banks in Kuwait. (2017) - Ltaifa, Monia Ben; Khoufi, Walid
Financial crises have highlighted the fragility of the banking system, especially for the case of conventional and Islamic banks. So, the objective of this paper is to verify the existence of the contagion effect between Islamic and conventional banks in Kuwait. Then, we use the dynamic conditional correlation-generalised autoregressive conditional heteroscedasticity (DCC-GARCH) model to estimate the conditional dynamic correlation to assess the financial contagion for a sample composed of three Islamic banks and five conventional banks during the period of study from 31 March, 2004 to 18 March, 2014. The empirical results show that the correlation between the returns of Islamic and conventional banks in Kuwait increased between the period of calm and crisis. This finding implies the existence of a contagion effect between Islamic and conventional banks in Kuwait. Also, thus result implies that financial contagion represents a major source for the spread of the crisis between the Islamic and conventional banks in Kuwait.